2016
DOI: 10.1007/s00425-016-2642-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of oxidative burst in sugarcane smut-resistant and -susceptible genotypes

Abstract: Smut pathogen induced an early modulation of the production and scavenging of reactive oxygen species during defence responses in resistant sugarcane that coincided with the developmental stages of fungal growth. Sporisorium scitamineum is the causal agent of sugarcane smut disease. In this study, we characterized sugarcane reactive oxygen species (ROS) metabolism in response to the pathogen in smut-resistant and -susceptible genotypes. Sporisorium scitamineum teliospore germination and appressorium formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 64 publications
(83 reference statements)
4
54
1
Order By: Relevance
“…Following sexual mating, dikaryotic hyphae with two compatible nuclei are formed and these hyphae are infectious (Sundar et al, 2012). The dikaryotic hypha grows along with sugarcane bud meristem and eventually forms the appressorium on the inner scales of the young buds (Peters et al, 2016). The two compatible nuclei then fuse and give rise to a diploid teliospore.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following sexual mating, dikaryotic hyphae with two compatible nuclei are formed and these hyphae are infectious (Sundar et al, 2012). The dikaryotic hypha grows along with sugarcane bud meristem and eventually forms the appressorium on the inner scales of the young buds (Peters et al, 2016). The two compatible nuclei then fuse and give rise to a diploid teliospore.…”
Section: Introductionmentioning
confidence: 99%
“…The two compatible nuclei then fuse and give rise to a diploid teliospore. A round of meiosis occurs during teliospore germination and generates four haploid sporidia (Sundar et al, 2012;Yan et al, 2015;Peters et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raffinose accumulation is an attractive candidate strategy together with the antioxidant system to restrain plant cell damage. Peters et al (2017) did not detect membrane damage in their experiments in any of the genotypes analyzed (susceptible and resistant).…”
Section: Discussionmentioning
confidence: 87%
“…Sugarcane is known to promote oxidative burst in response to smut infection (Lao et al, 2008; Su et al, 2014; Peters et al, 2017). Recently, detailed analysis of ROS metabolism revealed that a sugarcane resistant genotype maintained high levels of oxygen peroxide by a SOD independent pathway potentially to activate defense responses (Peters et al, 2017). Raffinose accumulation is an attractive candidate strategy together with the antioxidant system to restrain plant cell damage.…”
Section: Discussionmentioning
confidence: 99%